Comparison of non-invasive sampling methods for detection of HPV in rural African women. Issue 3 (27th May 2005) - Lack, N; West, B; Jeffries, D; Ekpo, G; Morison, L; Soutter, W P; Walraven, G; Boryseiwicz, L
Abstract : Background: The prevalence of cervical cancer is extremely high in low income countries, primarily because of a lack of cytological screening. The link between human papillomavirus (HPV) and cervical cancer has long been recognised, and it has been suggested that isolated HPV testing in women who do not participate in existing screening programmes may be used to identify women at higher risk of developing cervical cancer. This community based study compares two self administered techniques for detecting HPV (tampons and self administered swabs) with a clinician directed technique, the cervical cytobrush. Methods: 377 rural women were interviewed and of these 210 women had full gynaecological examination, and accepted all three sampling methods for HPV. HPV typing of DNA extracts was performed using polymerase chain reaction and enzyme linked immunosorbent assay techniques. Results: Using the cervical cytobrush as the gold standard, self administered swabs (SAS) showed a sensitivity of 63.9%, and tampons showed a sensitivity of 72.4%. The acceptability of these two tests was 97.1% and 84.6% respectively. When combining acceptability with sensitivity, the SAS detected 61.9% and the tampons detected 60.9% of the true positives. Conclusion: In a setting where women are at a considerable risk of developing cervical cancer, with no access to a formal screening programme, self directed HPV testing could be a useful screening tool in identifying those women at increased risk who may require further investigation.